Forsa pilot program and evaluation plan - El Shabrawy, Atef; Gilligan, Daniel O.; Kurdi, Sikandra; Palloni, Giordano; Yassa, Basma (International Food Policy Research Institute, 2022)
Forsa, which means “Opportunity” in Arabic, is a new economic inclusion program of the government of the Arab Republic of Egypt. Implemented by the Ministry of Social Solidarity, the program aims to graduate beneficiaries of the national cash transfer program, the Takaful & Karama Program (TKP), from being dependent on transfers from TKP to economic self-reliance by enabling them to engage in wage employment or sustainable economic enterprises. The most recent World Bank Economic Inclusion report (Andrews et al. 2021) highlights a recent increase globally in such graduation or economic inclusion programs, which now reach around 92 million beneficiaries from 20 million households across more than 75 countries. This rapid growth is raising demand for evidence on best practices in graduation program implementation. Egypt’s experience with Forsa can contribute to such guidance.